Improving the Empowerment of Breeders with Base of Local Problem Potency through Student Service Learning - Anna Fatchiya; . Jakaria (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Community empowerment activities of breeders by Bogor Agricultural University students in the form of Student Service Learning (CSP) in Lebak District is intended to improve their empowerment. In particular the purpose of CSP is to identify the potency and problems faced by breeders, to carry out community empowerment activities of breeders, and to analyze the impact of these activities. Activity methods include identification of potentials and problems, discussions, practices, and simulations. The results of this empowerment activity shows that the potential of livestock that can be developed in Lebak Regency is cattle, buffalo, goat, and chicken. But the obstacle is the knowledge of breeders on the management of livestock raising is still low, especially in the prevention of livestock disease, appropriate feeding, livestock waste management, and livestock processing. Implementation of community empowerment activities based on the results of identification process of potential and problems. Furthermore, it is done by using various methods, in the form of lectures, discussions and practices. The objective of the activity also focus to management as a whole and extends to the young generation and housewives, such as livestock education for school age children and livestock processing (nugget) for women. These activities have a positive impact on the community, such as improving the knowledge and skills of the community in managing their livestock business, such as arranging cages, feeding, processing of animal waste into organic fertilizer, processing of livestock products into fast food, and increasing knowledge and interest of young people in the field farming through counseling to school-aged children. The follow-up is to intensify this activity by the residents themselves and facilitated by extension workers and village officials, so that it adopted by many breeders.